Disease relapses in multiple sclerosis can be influenced by air pollution and climate seasonal conditions - Vojinović, Slobodan; Savić, Dejan; Lukić, Stevo; Savić, Ljiljana; Vojinović, Jelena (Vojnosanitetski pregled, 2014)
Background/Aim. Environmental factors may influence the disease activity in patients with relapsing-remitting multiple sclerosis (MS). The aim of this study was to evaluate the influence of air pollution and seasonal climate factors of any on number of relapses in MS patients during a consecutive 5 years of observation. Methods. We retrospectively analyzed data of MS patients from the town of Niš, hospitalized at the Clinic of Neurology, Clinical Center Niš, Serbia, from 2005 to 2009. Climate data: mean daily sun shining; mean monthly sun shining, mean whole daily cloudiness, daily cloudiness at 7 a.m, 2 p.m. and 9 p.m. and air pollution expressed by NSR (New Source Review) were obtained from the Meteorology Observatory Niš. Results. During a 5-year of observation there were 260 relapses in 101 MS patients. The number of relapses showed a significantly negative correlation with the number of days with NSR < 2 (ρ = -0.31; p < 0.01) and a positive correlation with the mean whole daily cloudiness (p < 0.05), mean daily cloudiness at 7 a.m. (p < 0.05) and 2 p.m. (p < 0.01). We found a significantlly positive correlation (p < 0.05) between the reduced number of relapses during the period of high vitamin D season, i.e. July–October. There was a statistically significant increase (p < 0.01) of the number of relapses during spring (ґ = 6.53; SD = 3.98) compared to the other three seasons. The joint presence of lower number of days with NSR < 2 during low vitamin D season (January–April) correlated with a statistically significant increase of the number of relapses in MS patients (F = 5.06, p < 0.01). Conclusion. The obtained results confirmed the influence of air pollution and climate seasonal conditions on disease relapses in MS patients based on a long-term observation. Lower numbers of days with low air pollution during the periods with low vitamin D (January–April), especially with increased cloudiness at 2 p.m, induce a higher risk of MS relapses in southern continental parts of Europe.